2020
DOI: 10.1002/adfm.202009394
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Mg2+ Displacement Driven Reversible Copper Extrusion/Intrusion Reactions for High‐Rate Rechargeable Magnesium Batteries

Abstract: Rechargeable magnesium batteries (RMBs) based on metal Mg anodes have shown great potential owing to the abundant natural resources, high volumetric capacity, and low safety hazard. Nevertheless, the development of RMBs is hampered by the sluggish kinetics of Mg2+ diffusion and the limited cyclability of cathode materials. Herein, nonstoichiometric copper selenide (Cu2–xSe) are synthesized via a solution‐based method and exploited as a durable cathode material based on ionic displacement mechanism for RMBs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 36 publications
1
56
0
Order By: Relevance
“…d) Specific capacity and gravimetric energy density values of the as-prepared FeS 2 cathode and some previously reported metal chalcogenide cathodes in RMBs or hybrid batteries using Mg metal anode. [4,[16][17][18][19][20][21][22]33,59,[65][66][67][68][69][70][71][72][73][74][75] e) Cycling performance of the FeS 2 cathodes at 200 or 400 mA g −1 after activation of 15 cycles at 50 mA g −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…d) Specific capacity and gravimetric energy density values of the as-prepared FeS 2 cathode and some previously reported metal chalcogenide cathodes in RMBs or hybrid batteries using Mg metal anode. [4,[16][17][18][19][20][21][22]33,59,[65][66][67][68][69][70][71][72][73][74][75] e) Cycling performance of the FeS 2 cathodes at 200 or 400 mA g −1 after activation of 15 cycles at 50 mA g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] However, the design of high-energy-density RMBs requires the development of high-performance magnesium-free cathode materials by using the Mg metal anode. [11,12] Various cathode materials, including transition metal oxides, [13][14][15] transition metal chalcogenides, [16][17][18][19][20][21][22][23] chalcogens, [24][25][26][27] transition metal halides, [28] halogens, [29] and polyanion-based compounds, [30,31] have been investigated for magnesium storage. Considering the strong polarization effect of the multivalent magnesium ion with a small ionic radius, cathode materials of chalcogens (e.g., S and Se) [27,32] and chalcogenides (e.g., TiS 2 , Cu 2 Se, CuS, and VS 4 ) [18,19,22,33] have attracted considerable attention due to the lower electronegativity of chalcogen anions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty lies in the strong coulombic interaction between highly polarized Mg 2+ ions and the cathode host, which might inevitably result in sluggish solid-state diffusion of the latter and slow interfacial charge transfer, thus causing poor electrochemical performance of RMBs. Besides the intercalation-type cathodes which have been studied extensively but yield a relatively low specific capacity and poor cycling life, 11 conversion-type materials, such as CuS, 12 CuSe, 13 CoS, 14 Ag 2 S, 15 and AgCl, 16 are promising cathode candidates for RMBs considering their high theoretical capacity and appropriate voltage platform. Nevertheless, conversion-type materials for RMBs still suffer from several drawbacks including poor intrinsic electrical conductivity, huge volume expansion, and nanoparticle aggregation, which imperatively need to be further resolved.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address those issues, many studies have been reported, in which the synthesis of yolk-shell structure hosts is considered to be a potential strategy [8][9][10]. Zhang et al reported a yolk-shell ZnO by using a hydrothermal method, which provided a specific capacity of 1406 mAh g −1 at 0.1C [11].…”
Section: Introductionmentioning
confidence: 99%